(untitled) (Journal of the College of Basic Education, 2023)
Al-Khadra or Green Island is located near Gibraltar at the southernmost tip of Andalusia, on a hill overlooking the Mediterranean Sea. And overlooking the Strait of Gibraltar (). It is an ancient city built by the Romans. In Roman times it was called Julia Ioza (). Geographical sources indicate that the Green Island is distinguished by its geographical location, moderate climate, and abundance of its resources. Remember that it is a sea city that enjoys a safe anchorage for travel, which is considered one of the easiest Andalusian anchorages for the neighborhood and the closest to the Moroccan state, as it faces the city of Ceuta on the Moroccan coast (). It is also a land of cultivation, udder and production, and it is flooded with fresh water, and it includes a small river called Wadi al-Asal (in Spanish (ROI). DELA MIEL,